Staphylococcal scalded skin syndrome in six children - Ruszkowska, Lidia; Dziekan, Grażyna; Olechowska, Magdalena (Dermatology Review/Przegląd Dermatologiczny, 2009)
Introduction. Staphylococcal scalded skin syndrome (SSSS) is regarded as a rare disease observed mostly in babies and small children. Objective. Presentation of 6 cases of SSSS hospitalized in the Paediatric Dermatology Unit between March 2008 and January 2009. Case reports. Six cases (one girl and 5 boys) at the age of 1 month to 3 years, with variously pronounced skin involvement characteristic of SSSS were admitted to the Paediatric Dermatology Department in a period of 10 months. Before admission, only two children were diagnosed as having SSSS, while in 4 cases toxic epidermal necrolysis or allergic dermatitis was recognized and children were treated with systemic corticosteroids without effect. In all cases Staphylococcus aureus from nose, pharynx, conjunctiva or urethra was cultured. Systemic therapy with antibiotics (cephalosporins) and local antibacterial and anti-inflammatory treatment provided remission of skin lesions in 6–9 days. Conclusions: Our observations indicate that staphylococcal scalded skin syndrome is not so rare but is a frequently misdiagnosed disease. It should be stressed that systemic antibiotic therapy is mandatory, while treatment with corticosteroids may worsen the course and prognosis in this syndrome.